Pengaruh Intensitas Modal dan Leverage terhadap Agresivitas Pajak: Studi Kasus pada Perusahaan Sektor Industri Barang Konsumsi yang Teraftar di Bursa Efek Indonesia Periode 2020-2023 - Lady Trifena Masa; Tirta Rangga Datu; Sita Yubelina Sabandar; Yohanis Tasik Allo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
To be able to reduce corporate tax payments, it is necessary to conduct an evaluation of tax management. Companies can exercise tax aggressiveness to minimize their tax burden without going against existing government policies. This study aims to examine the influence of capital intensity and leverage on tax aggressiveness. The population of this study is companies in the consumer goods industry sector listed on the Indonesia stock exchange for the 2020-2023 period. In collecting samples using the purposive sampling method, then there were 108 samples obtained. The research data used is secondary data in the form of annual financial reports from sample companies. The data analysis methods are classical assumption tests and hypothesis tests. The results showed that the capital intensity variable had a significant influence on tax aggressiveness, while the leverage variabel has an influence but not significantly on tax aggressiveness.